AMPK Activation in TET2 Downregulated Leukemia Cells Upon Glutamine Limitation - Ahsen Merve BAYRAK; Burcu YUCEL (Medeniyet Medical Journal)
Objective: Metabolic rewiring is a characteristic of cancer cells. Cancer cells require more nutrients for survival and proliferation. Although glutamine can be produced in cells via a series of enzymatic reactions, a group of cancer cells are dependent on extracellular glutamine for survival. TET2 plays a role in DNA demethylation and is a tumor suppressor gene. The TET2 gene is frequently mutated in various cancers, including acute myeloid leukemia (AML). Our study aimed to investigate the association between TET2-knockdown AML cell line HL-60 cells and glutamine metabolism. Methods: To evaluate the association between TET2 expression and glutamine limitation, TET2 was downregulated in HL 60 cells using shRNA plasmids. The proliferation of TET2-knockdown HL-60 cells was calculated in normal and glutamine deficient medium. GLUL mRNA expression was investigated using quantitative reverse transcription polymerase chain reaction and protein levels were evaluated using immunoblotting. Results: The numbers and viability of TET2-knockdown HL-60 cells were decreased in low glutamine-containing medium, but the viability of TET2-knockdown HL-60 cells was higher than that of control cells. GLUL mRNA expressions were increased in TET2- knockdown cells in low glutamine. In addition, P-AMPKα protein expression was increased in TET2-knockdown HL-60 cells in low glutamine-containing medium. Conclusions: Our findings indicate that TET2-knockdown HL-60 cells may be more resistant to glutamine deprivation. In glutamine-deficient medium, the mRNA expression of glutamine synthetase is increased, which could be related to glutamine addiction in cells. In addition, low-glutamyl medium increased the P-AMPKα protein level in TET2-knockdown HL-60 cells.